The Islamic State" in the Context of Political Changes in the Middle East - A. A. Kuznetsov (Vestnik MGIMO-Universiteta)
The article "The Islamic State phenomenon in the framework of the political changes in the Middle East" is dedicated to the "Islamic State", one of the most powerful and dangerous extremist organizations. Author realizes in this article: research of the genesis and causes of appearance of the movement "Islamic State"; analysis of the sociopolitical and geopolitical situation of the Iraqi Sunni community after the American invasion of 2003; bringing to the light factors of the high scale propagation of the Islamic extremism in Syria and Iraq; research of the military and political potential of the "Islamic State" and factors which could impede its expansion. Author considers "Islamic State" as an emergent phenomenon giving huge impact on the political situation in the Middle East. It provoked repartition of the old frontiers existed since the Sykes-Pico treaty of 1916. To the author's opinion oppression of the Iraqi Sunni community by the government of Nuri al-Maliki was the main cause of the Sunni revolt in Summer of 2014. Sunni tribes of Northern Iraq and former Baath party members were the driving forces of the revolt but then Jihadi extremists hijacked this revolt. To the author's mind elimination of the "Islamic State" is impossible without reconciliation between various religious communities in Syria and Iraq.